Mechanistic advances in factors influencing phenotypic variability in cerebral autosomal dominant arteriopathy with subcortical infarcts and leukoencephalopathy: a review - Zhao, Ying; Lu, YaRu; Wang, FengYu; Wang, YaDan; Li, YaQiong; Sun, RuiHua; Shang, JunKui; Jiang, Chao; Zhang, Jiewen (Frontiers in Neurology, 2025)
Cerebral autosomal dominant arteriopathy with subcortical infarcts and leukoencephalopathy (CADASIL) is a monogenic cerebral small-vessel disease caused by mutations in NOTCH3 and is the most common hereditary cerebral small-vessel disease in adults. The clinical manifestations of CADASIL include migraines, recurrent ischemic stroke, progressive cognitive deterioration, and psychiatric symptoms. The most prevalent and earliest imaging alterations in CADASIL are white matter hyperintensities in the periventricular white matter, temporal pole, external capsule, frontoparietal white matter, and other areas on magnetic resonance imaging. Despite the substantial variations in the clinical phenotypes and disease severity in patients with CADASIL, the specific mechanisms underlying these differences remain unclear. Exploring these underlying mechanisms is crucial for enhancing our understanding of CADASIL and offering insights into its early diagnosis and treatment. This review explores the advances in research on the molecular mechanisms contributing to the variability in clinical phenotypes and disease severity among CADASIL patients with different mutations.